The development of psychological talent in U.S. Olympic champions - Gould, D.; Dieffenbach, K.; Moffett, A. (Michigan State University, University of North Carolina, 2001)
Although considerable research has been conducted on the psychological characteristics of more versus less successful elite athletes (see Hardy, Jones, & Gould, 1996; and Williams & Krane, 2001, for detailed reviews), less is known about how these skills are cultivated and developed. Several large-scale studies (Bloom, 1985; Csikszentmihalyi, Rathunde, Whalen, & Wong, 1993) on talent development across a variety of domains (e.g., music, art, science, sport) have been conducted, however. Findings showed that to turn talent into actual achievements, individuals must develop specific psychological skills, orientations, and habits and have the opportunity to develop their mental and physical skills in supportive environments comprised of significant others who provide various types of support. More recently, Côté (1999) studied the influence of athletes` families on the development of talent in sport, finding that they played an extremely important role. Expanding on this initial research, this study was designed to examine the process of psychological talent development in Olympic medal winning athletes. In the present study, 10 current or former U.S. Olympic champions with outstanding performance records over time (winners of 28 Olympic gold, three silver, and one bronze medals) were interviewed, as were one of their coaches (n = 10), and a parent, guardian, or significant other (n =10). Questions focused on the psychological and emotional attributes of the athlete, the process by which these attributes developed, and the culture supporting his or her psychological talent development. A battery of psychological inventories (trait anxiety, hardiness, perfectionism, optimism, trait hope, sport motivation, task and ego goal orientation, psychological skills and strategies, and coping) was also administered to each athlete to identify his or her psychological strengths. Descriptive statistics were used to examine the psychological inventory quantitative data related to the psychological characteristics of the athletes. Psychological strengths and limitations were determined by examining the magnitude of the participant`s responses. In cases where elite athlete norms existed, participant scores were compared to existing norms for elite athletes. Results revealed that these athletes exhibited low levels of Sport Anxiety Scale (Smith, Smoll, & Schultz, 1990) somatic (M =16.7 out of 36) and worry (M = 11.2 out of 36) trait anxiety. They also exhibited high agency hope--the ability to begin and continue along a selected goal pathway (M = 29.1 out of 32) on the Adult Trait Hope Scale (Snyder, Cheavens, & Michael, 1999). Relative to multidimensional perfectionism (Frost, & Henderson, 1991), the athletes scored high in an absolute level on adaptive perfectionism subscales (M personal standards = 28 out of 35, M organization = 24 out of 30) and low on maladaptive subscales (M parental expectations = 12 out of 25, M parental criticism = 6.0 out of 20, M doubts about actions = 8 out of 20). Sport Motivation Scale (Pelletier, Fortier, Vallerand, Tuson, Briere, & Blais, 1995) results showed that the athletes exhibited very high levels of intrinsic motivation -- to know (M = 18.7 out of 28), to accomplish (M = 23.3 out of 28), and to experience simulation (M = 21.5 out of 28). On the Athletic Coping Skills Inventory - 28 (Smith, Schultz, Smoll, & Ptacek, 1995), the Olympians scored one standard deviation higher on goal setting and mental preparation (M = 9.2 out of 16) compared to professional baseball players (M = 6.56). Taken together, these findings verify current sport psychological research on psychological characteristics associated with peak performance (Hardy, Jones, & Gould, 1996; Williams & Krane, 2001). They also suggest that adaptive perfectionism, hope, and optimism are especially important new variables associated with elite athletic success. Qualitative data was analyzed using hierarchical content analysis (Gould, Eklund, & Jackson, 1993; Gould, Jackson, & Finch, 1993a; 1993b; Gould, Greenleaf, Dieffenbach, Lauer, Chung, Peterson, & McCann, 1999), triangulating across data sources (athletes, coaches, and parents). Characteristics of champions identified by the participants in the open-ended interviews triangulated most of the quantitative findings. Specifically, these champions were characterized by the ability to focus, high optimism, mental toughness, drive, competitiveness, confidence, sport intelligence, coachability, and the ability to handle stress. Major motives for involvement included achievement/ competence, fun and enjoyment, love of the sport, achieving the Olympic dream, and affiliation. Motives were found to vary to some degree across Bloom`s (1985) phases of talent development. Relative to the series of questions asking what factors influenced the psychological development of these champion athletes; results showed that many individuals and institutions were perceived to influence the development of these outstanding performers. Specifically, sources of influence included the community, family, non-sport personnel, the individual him or herself, sport environment/ personnel and the sport process. Moreover, modes of influence were both direct, such as teaching or emphasizing certain psychological lessons, and indirect involving modeling or unknowingly creating certain psychological environments. These results, then, supported the work of Bloom (1985) and Csikszentmihalyi and colleagues (1993) in showing that the psychological development of outstanding athletes takes place over a long time period and is influenced by a variety of individuals and factors. This long-term process involves both the talented person and a strong support system. Not surprisingly, parents and families were perceived to play a critical role in psychological talent development. They were found to provide financial, logistical, and social-emotional support. Specifically, parents were very committed to their child and did such things as modeled an active life style, exposed their child to different sports, transported their child, attended games and practices, and provided considerable encouragement and unconditional support. While families clearly supported and encouraged participation, in most cases they exerted little pressure to win. Families also emphasized an optimistic belief in the child`s ability to succeed or a "can do" attitude. Families also modeled hard work and discipline, a finding consistent with research by Monsaas (1985), Sloboda & Howe (1991), Sloan (1985), and Sosniak (1985), who showed that parents of highly successful individuals espoused or modeled values related to achievement such as hard work, success, and being active and persistence. At the same time, parents emphasized the notion, "if you are going to do it, do it right". They also held high (but reasonable) expectations and standards for their child, and a stick to it and follow-through on commitments attitude. These results are consistent with Bloom`s (1985) conclusion that the successful development of a talented individual requires the facilitation of disciplined involvement while avoiding excessive expectations. This is also consistent with Csikzentmihalyi et al.`s (1993) complex family notion. That is, these families are both integrated and differentiated. Integrated in that they were stable in their sense of support and consistency. Differentiated in that they encouraged their children to "individually" seek out new challenges and opportunities. Finally, in the early phase of the athlete`s career, the majority of these parents did not have winning or the Olympic Games as an objective of participation. Instead, they focused on their child`s happiness, a balance of fun and development, and the general developmental benefits of participation. While there was some emphasis on winning and success, these were not the predominant objectives of participation. At the same time, parents emphasized working hard, having a positive attitude, and discipline. Throughout the middle and elite phases of the athlete`s career, many parents also played an important role in helping the athlete keep winning and success in perspective. The roles of the parents also changed over time (from leader to follower role over three phases) supporting the research of Côté (1999). Like parents, coaches were also found to be a primary influence on athlete psychological development. They did this in a number of ways including emphasizing certain things such as hard work and discipline or having fun, having characteristics that facilitated athlete trust, providing encouragement and support, directly teaching or fostering mental skills, and by understanding these athletes. Looking across the interviews, it was also clear that the same coaching strategies were not appropriate for each athlete, different athletes required different things from their coaches at different points in their careers. This emphasized the importance of coaches reading athletes` psychological needs and utilizing different approaches at different times and in different situations. Establishing a strong coach-athlete relationship was critical for these champions. This was reported as being especially important in the middle and elite years. Participants indicated that key factors in this relationship involved coach credibility (e.g., elite status, knowledge), reciprocal trust and respect, understanding athlete needs and responding accordingly, and caring about the athlete as a person and not just a performer. In terms of Bloom`s career phases, a win focus on the part of coaches did not emerge for most athletes until the middle years. Fun and development were stressed in the early years. High expectations and standards, hard work, and discipline seemed to be especially important coaching practices in the last two phases. Lastly, it was interesting to note that many of the participants mentioned that early coaches did not "damage" the young athlete psychologically, verifying the conclusion that youth coaching can have an important effect on the psychological development of elite competitors. The importance of coaching psychology emerges from these findings. Coaches were reported to create motivational climates that "pushed" these champions in "good" ways. It was also reported that the coaches played an important role in helping the athletes keep success in perspective. Finally, the coaches were very involved in teaching these athletes mental skills such as imagery, goal setting, and mental preparation. This, then, certainly emphasizes the importance of elite level coaches being well versed in psychological skills training. In summary, a better understanding of psychological talent development and the factors that influence psychological talent development was gained in this study. The findings and their implications are discussed relative to previous athlete talent development studies (Bloom, 1985; Csikszentmihalyi, Rathunde, Whalen, & Wong, 1993; Côté, 1999; Durand-Bush & Salmela, 2001) and psychology of peak performance research (Hardy, Jones, & Gould, 1996) is emphasized. Practical implications and future directions are also emphasized.